Concrete and dirt surfaces compared for fattening beef cattle - Drake, C.L.; Smith, E.F.; Perry, H.B.; Lipper, R.I.; Larson, G.H. (Kansas Agricultural Experiment Station, 2011)
The Animal Husbandry and Agricultural Engineering departments cooperate in this project. The response of cattle with water applied as “artificial rain” on a concrete and a dirt surfaced lot is being studied. Ways to collect and handle feedlot runoff also are being studied. Two lots identical in size (42’ x 92’) were used. The dirt lot had a 16’ x 24’ concrete apron; both lots had fence-line bunks. Two trials are reported.
Keywords: Beef; Rainfall; Feedlot runoff; Artificial rainfall